Strategies For Strengthening Social Capital In Rubber Farming Communities In Facing Disaster In Lake Village, Nalo Tantan District - Zusmelia, Zusmelia; Irwan, Irwan; Amelia , Anggun; Virginia, Delia (International Journal of Educational Research & Social Sciences, 2022)
In general, the purpose of this study is to analyze the strategy of strengthening social capital in farming communities in dealing with disasters in Lake Village. In particular, the purpose of this study is to analyze the forms of social capital of rubber farmers and strategies for strengthening social capital of rubber farmers in dealing with landslides in Danau Village. This study uses a qualitative approach with a descriptive type. The informants of this research are people who experience disasters in Danau Village. The unit of analysis is at the community level or including the meso level. The data collection method was carried out in several stages, namely non-participant observation, in-depth interviews and document studies. Data analysis uses Miles & Huberman model thinking. The results of this study indicate that the form of social capital that is built in disaster areas is to strengthen norms in society, cooperate with each other, conduct mutual social interactions, build government-level networks and have a caring attitude among disaster victims. The strategy for strengthening social capital is built on the value of togetherness and mutual trust based on disaster-safe areas as a source of economic strengthening for rubber farmers. Novelty in this study is social capital to build disaster-safe areas.